The Impact of the Lactation Period Gut Microbiota of Two Different Beef Cattle Breeds on Spring-Born Calves - Changbo Chen; Yuzhu Sha; Xiaoqiang Zhang; Pingle Lu; Jianyuan Gao; Ting Jiao; Shengguo Zhao (Animals)
To investigate the impact of maternal microbiota during lactation in different beef cattle breeds on their own immune levels, milk quality, and the growth and development of their offspring, this study measured the immune parameters, intestinal microbiota diversity, and milk quality of Pingliang red cattle and Simmental cattle, and performed a correlation analysis with the growth and development of their offspring. Our study showed that during lactation, Pingliang red cattle had significantly higher IL-6 levels than Simmental cattle, while the latter exhibited higher levels of immune factors such as IgG, IgA, IgM, IL-1β, and TNFα. The analysis of the intestinal microbiota of lactating cows found that Pingliang red cattle were rich in Bacteroidetes and Fibrobacteres, while Simmental cattle had a higher proportion of Actinobacteria. This difference may be related to the different adaptation strategies in energy metabolism and immune regulation between the two breeds. In addition, the analysis of milk quality between different beef cattle breeds revealed significant differences in protein, acidity, milk fat, and total solids. The correlation analysis found that Alistipes_communis, Firmicutes_bacterium_CAG_110, Alistipes_communis, Paludibacter_propionicigenes, Alistipes_sp._58_9_plus, and Bacteroidales_bacterium_55_9 were associated with both milk quality and the growth of offspring calves, including body weight, body length, chest girth, and cannon circumference. In conclusion, this study provides new insights into the intestinal microbiota, immune characteristics, and their effects on offspring health in different beef cattle breeds, and has important implications for breed selection and management strategies in the livestock industry.